SISTEM MANAJEMEN PENGETAHUAN PERLINDUNGAN ANAK (STUDI KASUS: SAKTI PEKSOS DI KEMENTERIAN SOSIAL) - Ahmad, Tarmizi; Hermadi, Irman; Kusuma, Wisnu Ananta (Puslitbangkesos Kementerian Sosial RI, 2019)
In 2014, The Ministry of Social Affairs ofThe Republic of Indonesia (MOSA) send 670 social workers, called ?Sakti Peksos? to all provinces in Indonesia. Sakti Peksos, which stands for ?Satuan Bakti Pekerja Sosial? is the social workers who assist the Child Welfare Program in Indonesia or known as ?PKSA?. To assist the children?s case, the social workers need many practice knowledge of how to deal with the children?s issues. Therefore, it is beneficial to manage the existing information by developing knowledge management system. Through the application based web program, this knowledge management system will develop all the Sakti Peksos?s knowledge. This web aims at organizing all the informations that they have so that it can be shared to other Sakti Peksos. The purpose of this study was to develop a Child Protection Knowledge Management System for Sakti Peksos in the Ministry of Social Affairs. This research uses Knowledge Management System Life Cycle methodology which is adopted from award and ghaziri methodology. This research involves four steps; gathering the knowledge, designing the brueprint of knowledge management system, helding verification as well as validation process, and implementing knowledge management system. The result of this research is a web based child protection knowledge management system, equipped with CakePHP framework and MySQL as Relational Database Management System (RDBMS).